SOSIALISASI TENTANG PEMBAGIAN WARISAN MENURUT HUKUM ADAT DAN HUKUM PERDATA DI DESA KUAKLALO KECAMATAN TAEBENU - Nubatonis, Orpa Juliana; Bire, Chatryen M. Dju; Jacob, Yossie M. Y.; Dinata, Husni Kusuma; Renda, Ariance (Universitas Mataram, 2024)
Inherited property is defined as that which is left by the testator to be distributed to his heirs. In Indonesia, the law of inheritance distribution is governed by three legal systems: customary inheritance law, Islamic inheritance law, and inheritance law based on the Civil Code. The community service team identified a lack of understanding about the division of inheritance according to customary law and civil law in Kuaklalo Village. The proposed solution is to provide an explanation of the division of inheritance according to customary law and civil law. The objective of this activity is to offer an explanation to the local community regarding the division of inheritance according to customary law and civil law. The method employed is through the socialization of material delivery and direct question-and-answer discussions with the local community. The stages of activities that will be carried out are as follows: (a) The preparation stage includes: (1) survey, (2) deliberation, (3) preparation of socialization materials. (b) The implementation stage. The local community members who participated in this activity displayed a high level of enthusiasm, as evidenced by the questions and discussions they engaged in with the speakers on topics related to the challenges they face in their daily lives. In addressing the queries raised by the community regarding the distribution of inheritance, the resource person not only provided responses but also facilitated further dialogue with the lecturers who attended the activity. The findings of the dissemination activities conducted by the Community Service Team demonstrate that the knowledge and comprehension of the distribution of inheritance according to both customary law and civil law were enhanced. The Community Service Program offered an opportunity for participants to gain insights and understanding of the distribution of inheritance according to civil law and customary law.